Engineered Bone for Probing Organotypic Growth and Therapy Response of Prostate Cancer Tumoroids in vitro - Paindelli, Claudia (Biomaterials, 2019)
Mechanistic analysis of metastatic prostate cancer (PCa) biology and therapy response critically depends upon clinically relevant three-dimensional (3D) bone-like, organotypic culture. We here combine an engineered bone-mimetic environment (BME) with longitudinal microscopy to test the growth and therapy response of 3D PCa tumoroids. Besides promoting both tumor-cell autonomous and microenvironment-dependent growth in PCa cell lines and patient-derived xenograft cells, the BME enables in vivo-like tumor cell response to therapy, and reveals bone stroma dependent resistance to chemotherapy and BME-targeted localization and induction of cytoxicity by Radium-223. The BME platform will allow the propagation, compound screening and mechanistic dissection of patient-derived bone tumor isolates and applications toward personalized medicine.